2009
DOI: 10.1159/000242429
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in Allergic Rhinitis

Abstract: Background: Olfactory dysfunction in patients with allergic rhinitis has long been thought to be secondary to coexisting chronic rhinosinusitis and polyposis with obstruction of airflow over the olfactory epithelium. Recent evidence suggests that the allergic inflammatory infiltrate may itself affect olfaction in the absence of mucosal hypertrophy. Objective: We undertook a study to determine olfactory function in patients with allergic rhinitis in the presence and absence of chronic sinusitis. Methods: Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 30 publications
2
23
0
4
Order By: Relevance
“…Olfactory function was decreased in threshold, discrimination, and identification testing in patients with seasonal or perennial AR, which is in good accordance with other published studies [3,11]. Levels of ECP were significantly elevated in our patients, with seasonal AR being in line with comparable data published by Klimek et al [4], who showed eosinophilic inflammation of the nose after 3 weeks after the beginning of allergy season and Kramer et al [12] who compared ECP levels of different chronic nasal inflammatory diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Olfactory function was decreased in threshold, discrimination, and identification testing in patients with seasonal or perennial AR, which is in good accordance with other published studies [3,11]. Levels of ECP were significantly elevated in our patients, with seasonal AR being in line with comparable data published by Klimek et al [4], who showed eosinophilic inflammation of the nose after 3 weeks after the beginning of allergy season and Kramer et al [12] who compared ECP levels of different chronic nasal inflammatory diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Is it the whole inflammatory milieu with a mixture of different mediators from different kinds of cells or is it a single mediator leading to this lack of olfactory function? Current studies in humans [11] and in an animal model using allergic mice [15] showed an infiltration of eosinophils, neutrophils, mast cells, plasma cells, and macrophages in the olfactory mucosa. So far the available studies have mainly focused on the role of eosinophilic cells and their main toxic mediator in AR ECP.…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned above, Guss et al 54 showed in a small group of 31 patients with AR that 48% had measured olfactory dysfunction. However, none of their patients exhibited anosmia, indicating that olfactory dysfunction was not severe.…”
Section: Effect Of Ar On Olfactionmentioning
confidence: 78%
“…This is probably secondary to a local inflammation in the nasal fossa and around the olfactory neuroepithelium in the olfactory cleft rather than a nasal obstruction impairing the odours to reach the olfactory cleft [82]. …”
Section: Multi-morbidities Of Allergic Rhinitismentioning
confidence: 99%